Internalisasi Nilai-nilai Agama Islam Dalam Pembentukan Karakter Siswa Melalui Kegiatan ekstrakurikuler Keagamaan Di SMAI Miftahul Ulum Jatiurip Krejengan - Maryam, Siti; Sakdiyah, Muslimatus (LP3M UNZAH GENGGONG, 2019)
Abstract Education in Indonesia in the last decade has reaped many problems, one of which is by starting the loss of morality or character that engulfs the younger generation and this has become an important discussion that should be noted by all of us. As with many students who show the character that is considered unfavorable such as promiscuity or the other. Seeing this problem, it is necessary to have a number of breakthroughs, one of which is through internalization of Islamic religious values ​​implemented in schools, both through teaching in class and other activities such as religious extracurricular activities. Therefore, the researcher focused on the process and implications of internalizing Islamic religious values ​​at Miftahul Ulum Jatiurip Krejengan High School and hoped that they could be made as a solution in character formation. In this study using descriptive qualitative research. For data collection, researchers used observative methods, interviews, and also documentation using descriptive analysis to describe and paint the data obtained. Keywords: Internalization of Islamic Religious Values, Student Character, Religious Extracurricular Activities